Transcutaneous Auricular Vagus Nerve Stimulation Modulates the Prefrontal Cortex in Chronic Insomnia Patients: fMRI Study in the First Session - He, Jia-Kai; Jia, Bao-Hui; Wang, Yu; Li, Shao-Yuan; Zhao, Bin; Zhou, Zeng-Guang; Bi, Yan-Zhi; Wu, Mo-Zheng; Li, Liang; Zhang, Jin-Ling; Fang, Ji-Liang; Rong, Pei-Jing (Frontiers in Neurology, 2022)
Abstract Objectives: Transcutaneous auricular vagus nerve stimulation (taVNS) has been reported to be effective for chronic insomnia (CI). However, the appropriate population for taVNS to treat insomnia is unclear. Methods: Twenty-four CI patients and eighteen health controls (HC) were recruited. Rs-fMRI was performed before and after a thirty minutes’ taVNS at baseline. The activated and deactivated brain regions were revealed by different voxel based analyses, then the seed- voxel functional connectivity analysis was calculated. Thirty minutes of taVNS was applied twice daily for 4 weeks in the CI group. Pittsburgh Sleep Quality Index (PSQI) and Flinders Fatigue Scale (FFS) were also assessed before and after 4 weeks of treatment in the CI group. The HC group reccived no any treatment. The correlations were estimated between the clinical scales’ score and the brain changes. Results: The socores of PSQI (p < 0.01) and FFS (p < 0.05) decreased after 4 weeks in the CI group. Compared to the HC group, the first taVNS session up- regulated left dorsolateral prefrontal cortex (dlPFC) and decreased the FCs between dlPFC and bilateral medial prefrontal cortex in the CI group. The CI groups’ baseline voxel wised fMRI value in the dlPFC were negatively correlated to the PSQI score and the FFS score after 4 weeks treatment. Conclusions: It manifests that there is a modulational effect for taVNS on the prefrontal cortex in patients with CI. The initial state of dlPFC may predict the efficacy for taVNS on CI.